Caracterização e avaliação de filmes metálicos para uso em ultra-alto vácuo - Ferreira, Marcelo Juni (Universidade Federal de São Carlos, 2007)
The construction of ultra-high vacuum chambers (UHV) for particle accelerators demands pressure in the range of 10-8 Pa, and this is particularly difficult to achieve in chambers with the length to traverse section rate of approximately 150:1. Among several methods used to obtain this condition, it stands out the internal coating with metallic films capable of absorbing gases, called NEG (Non-Evaporable Getter). These metallic films, cannot have gas molecules on the surface and should be deposited on the internal surface of the chamber, making it a vacuum pump. Usually these materials are constituted by elements of great chemical reactivity and solubility (such as Ti, Zr and V), at room temperature for oxygen and other gases typically found in UHV (H2, CO and CO2), besides having low oxygen temperature diffusion (< 700 K), the so called activation temperature. The objective of this work is to characterize and to evaluate TiZrV alloy and Au films produced by magnet sputtering for UHV application. The structure, morphology and aging of the films have been characterized in order to know how much of the gas absorption property at low temperature can be attributed to the structure formed by the deposition process and the chemical reactivity of the elements. The morphological, structural and chemical characterization was carried out by atomic force microscopy (AFM), high resolution scanning electron microscopy (FEG-SEM), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Rutherford backscattering spectroscopy (RBS) and photon stimulated desorption (PSD). The produced materials were compared with commercial TiZrV samples, and this comparison made clear that the desired characteristics are related to the nanometric structure of the films and that the structure is clearly sensitive to the heat treatments.
Characterization and evaluation of metallic films to be used in ultra-high-vacuum
Keywords: Metais; Filmes metálicos; Ultra-alto vácuo; Gases em metais; Gases - absorção e adsorção; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA